Characterization and mode of occurrence of rare earth elements and yttrium in fly and bottom ash from coal‑fired power plants in Java, Indonesia - Besari, Dea Anisa Ayu (Springer, 2022)
Fly and bottom ash (FABA) produced primarily from coal combustion in a coal-fired power plant consists of fine particles of the organic and inorganic mixture and trace elements. Eight FABA samples from coal-fired power plants in Java, Indonesia, had been collected for composition and rare earth element and Yttrium (REY) mode of occurrence identification. The geochemical composition of both major and trace elements was determined by inductively coupled plasma-mass spectrometry/ atomic emission spectrometry (ICP-MS/AES). Furthermore, the composition of FABA was identified by petrography with reflected light microscopy and X-ray diffraction (XRD) analysis. Simultaneously, scanning electron microscope determines the mode of occurrence of REY with an energy-dispersive X-ray (SEM–EDX). The study finds that the inorganic component of FABA consists of glass, Fe–Mg spinel, mullite, quartz, Fe-oxide mineral, and K-feldspar. In contrast, the organic component is dominated by unburned coal. Glass is the most abundant component with cenospheres as major and pleiospheres as minor constituents. Trace elements analysis indicates REY concentration with heavy REY (HREY) distribution pattern. Moreover, SEM–EDX analysis results show that Yttrium (Y) occurs in glass and has a low concentration in spinel. From the mode occurrence of REY, in particular Yttrium, it can be predicted that alkaline fusion followed by acid leaching will be the most appropriate extraction method to extract REY from Indonesian FABA.